Upper airway wheezing: Inducible laryngeal obstruction vs. excessive dynamic airway collapse - Rendo, Matthew (Respir Med Case Rep, 2019)
There are multiple causes of dyspnea upon exertion in young, healthy patients to primarily include asthma and exercise-induced bronchospasm. Excessive dynamic airway collapse (EDAC) describes focal collapse of the trachea or main bronchi with maintained structural integrity of the cartilaginous rings. It is commonly associated with pulmonary disorders like bronchiectasis, chronic obstructive pulmonary disease and asthma. It is believed to result secondary to airway obstruction in these conditions. While uncommon in young, healthy adults, it has recently been found as a cause of dyspnea in this population. Inducible laryngeal obstruction (ILO) is an umbrella term that describes an induced, intermittent upper airway impediment. While ILO is found in 10% of young patients with exertional dyspnea, it is primarily inspiratory in nature due to paradoxical closure of the glottis or supraglottis. This report highlights the presentation of a United States Army soldier who after a deployment was given a diagnosis of asthma, later found to have ILO and was subsequently diagnosed with concurrent EDAC. We follow up with a literature review and discussion of symptomatology, diagnosis, exercise bronchoscopy, and treatment modalities for both EDAC and ILO.